Young horticulturists, adult horticulturists. Approaches to the sense of youth in Bolivian migrant families who are dedicated to horticulture in Gran La Plata - Lemmi, Soledad; Morzilli, Melina; Castro, Andrea (Facultad de Ciencias Políticas y Sociales, 2020)
This work brings together a set of reflections on being young regarding the senses and identifications that families with a history of migration from Bolivia who are engaged in horticulture in Greater La Plata. Through ethnographic work using participant observation and in-depth semi-structured interviews, it was concluded that being young means practicing horticulture while studying, which is the main activity at that point in life, whereas being an adult means being a horticulturist, since work in the farm is the main concern. It was also noted the updating of the cultural heritage inherited from the past lived in Bolivia and how it operates in the construction of these meanings and identifications in the present.